Pengaruh Brand Ambassador dan Iklan Media Sosial Melalui Kepercayaan Penjualan terhadap Loyalitas Konsumen Tokopedia - Vivin Yuwansa; Ida Bagus Nyoman Udayana; Agus Dwi Cahya (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the effect of Brand Ambassadors and Social Media Ads Through Sales Trust on Tokopedia Consumer Loyalty. This study used a quantitative research type and selected 100 people (male & female, 18-30 years old, and using Tokopedia e-commerce) as research subjects. Researchers use the help of SmartPLS software version 3.2.9, where the results of the analysis will be described in tabular form. The results of the study show that the brand ambassadors chosen by Tokopedia have not been able to create direct consumer loyalty to their customers and have not contributed optimally in creating trust directly to consumers and sales trust is unable to become an intermediary or mediate brand ambassadors for consumer loyalty because brand ambassadors do not involve there is an influence on consumer trust and loyalty. Keywords: Brand Ambassador, Social Media Advertising, Sales Trust and Consumer Loyalty